(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
We have done the project over there are NAVIGATION and SURVILLANCE in Airport Authority of India(AAI).This paper deals that AAI provides CNS services at all Indian airports, including privately operated ones, and limited navigation services at defiance airfields. These include: Maintenance of CNS/air traffic management (ATM) system/equipment, calibration of flight and ground radio navigation aids, certification of CNS/ATM system/equipment, modification of operational CNS/ATM equipment, corrective maintenance, preventive maintenance; installation of CNS/ATM system/equipment, develop, review and modify CNS/ATM system/equipment, and/or maintenance procedures.